2003
DOI: 10.1167/iovs.02-0397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ion Transport and Channel-Blocking Drugs on Aqueous Humor Formation in Isolated Bovine Eye

Abstract: At least 60% of the AH is formed by active secretion in bovine eyes. Transport of anions through the ciliary epithelium (CE), particularly the chloride ion, plays a crucial role in AHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…The Na + ,K + -ATPase of PE cells probably differs functionally from that of NPE cells as reflected by the different isoforms shown in these two cell types (Ghosh et al, 1991). Pharmacological inhibition of Na,K-ATPase by ouabain caused 62% inhibition of aqueous humor secretion in an arterially perfused bovine eye indicating the major role played by this primary active transport system (Shahidullah et al, 2003). Transport systems for glucose, several amino acids (DiMattio et al, 1981;Hu et al, 2011;Reddy, 1979) and ascorbate (Chu and Candia, 1988) have been identified in the NPE.…”
Section: Molecular Entities Involved In Ah Secretionmentioning
confidence: 96%
See 1 more Smart Citation
“…The Na + ,K + -ATPase of PE cells probably differs functionally from that of NPE cells as reflected by the different isoforms shown in these two cell types (Ghosh et al, 1991). Pharmacological inhibition of Na,K-ATPase by ouabain caused 62% inhibition of aqueous humor secretion in an arterially perfused bovine eye indicating the major role played by this primary active transport system (Shahidullah et al, 2003). Transport systems for glucose, several amino acids (DiMattio et al, 1981;Hu et al, 2011;Reddy, 1979) and ascorbate (Chu and Candia, 1988) have been identified in the NPE.…”
Section: Molecular Entities Involved In Ah Secretionmentioning
confidence: 96%
“…This is in accordance with their ability to reduce AH formation in dogs (Maren, 1976) and rabbits (Caprioli and Sears, 1984;Kodama et al, 1985), species in which the CE concentrates bicarbonate from blood to aqueous and the AH is bicarbonate-rich. Curiously, however, the CAIs reduce aqueous formation equally efficiently in eyes where the concentration of bicarbonate in plasma and aqueous is similar in human (Dailey et al, 1982;Toris et al, 2004), monkey (Wang et al, 1991), bovine (Shahidullah et al, 2003) and pig (Shahidullah et al, 2009). There is no apparent net bicarbonate movement across the CE in these species, yet the CAIs reduce fluid formation.…”
Section: Medical Treatment Of Glaucomamentioning
confidence: 99%
“…As mentioned above, the large discrepancy between the in vitro measures of J v and the rates of aqueous humor formation does not by necessity demonstrate a large role for ultrafiltration in the in vivo production of aqueous humor; nor do the volumetric approaches with the CE provide any estimate of the relative proportions between secretion by the CE and ultrafiltration. An alternative, interesting arrangement for characterizing the mechanisms underlying aqueous humor formation involves the use of an in vitro perfused bovine eye (Shahidullah et al, 2003). With this methodology, a perfusion pressure is applied, and 40% of aqueous humor formation was ouabain insensitive (Shahidullah et al, 2003), suggesting that this may represent a proportion of the formation due to passive ultrafiltration.…”
Section: Fluid and Electrolyte Transport Studies On Isolated Ciliary mentioning
confidence: 99%
“…An alternative, interesting arrangement for characterizing the mechanisms underlying aqueous humor formation involves the use of an in vitro perfused bovine eye (Shahidullah et al, 2003). With this methodology, a perfusion pressure is applied, and 40% of aqueous humor formation was ouabain insensitive (Shahidullah et al, 2003), suggesting that this may represent a proportion of the formation due to passive ultrafiltration. However, Shahidullah et al (2003) point out that their resultant estimation of 40% ultrafiltration in aqueous humor formation may be an overestimation, because the inhibition of active transport processes with ouabain should have led to a reduction in the intraocular pressure, which would have favored more passive ultrafiltration of aqueous humor.…”
Section: Fluid and Electrolyte Transport Studies On Isolated Ciliary mentioning
confidence: 99%
“…Bovine eyes were perfused using a method described in earlier studies on aqueous humor formation and multifocal electroretinogram (Shahidullah et al, 2003(Shahidullah et al, , 2005. The ophthalmic artery was cannulated and the eye perfused with a physiologic saline.…”
Section: Methodsmentioning
confidence: 99%